Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Kinerja Karyawan PT. Indomarco Prismatama Cabang Kelapa Gading - Erlina, Eka Kartikasari; Purwatiningsih Purwatiningsih (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
Human resources (HR) play a crucial role in determining the success of an organization. PT Indomarco Prismatama is a leading company in the modern retail sector, operating the Indomaret minimarket network that provides essential daily needs for the community. Within this context, employee performance becomes a critical factor that directly influences business continuity and service quality. However, several issues remain, such as high absenteeism, low motivation, and disharmonious workplace relationships. These conditions highlight the importance of effective leadership styles and a strong organizational culture in enhancing employee performance. This study aims to analyze the influence of leadership style and organizational culture, both partially and simultaneously, on employee performance at PT Indomarco Prismatama, Kelapa Gading Branch. The research employed a quantitative approach with an associative design. The population consisted of 102 employees, with a sample of 81 respondents determined using Slovin’s formula. Data were collected through a Likert-scale questionnaire and analyzed using validity and reliability tests, multiple linear regression, t-tests, and F-tests to examine the relationships among variables. The findings reveal that leadership style significantly influences employee performance, while organizational culture also has a positive and measurable effect. Furthermore, the simultaneous influence of both variables shows a significant impact on improving performance. These results indicate that a combination of effective leadership and a supportive organizational culture plays a vital role in enhancing productivity and achieving organizational goals at PT Indomarco Prismatama, Kelapa Gading Branch.